2019
DOI: 10.1021/acsami.9b17623
|View full text |Cite
|
Sign up to set email alerts
|

Highly Intensified Molecular Oxygen Activation on Bi@Bi2MoO6 via a Metallic Bi-Coordinated Facet-Dependent Effect

Abstract: Construction of the semimetal/semiconductor composite interface is widely used to promote the O 2 molecule adsorption and charge transfer for boosting solardriven molecular oxygen activation (MOA). Herein, a Bi@ Bi 2 MoO 6 heterostructure is fabricated via a two-step wet chemical method as a typical photocatalyst to investigate the underlying mechanism of Bi-coordinated facet-dependent MOA under visible-light illumination. Density functional theory and systematical characterization methods reveal the distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…Meanwhile, the Fourier‐transform (FT)IR spectra displayed that the absorption bands of Bi−O bond and Mo−O bond of Bi 2 MoO 6 −Vo and Bi@Bi 2 MoO 6 are weaker than that of pure Bi 2 MoO 6 , indicating that both samples contain oxygen defects (Figure S3). Abundant oxygen vacancies on the surface of Bi 2 MoO 6 nanosheets not only change the chemical coordination of Bi 3+ ions to form metal nanoparticles, but also facilitate chemical adsorption of CO 2 molecules on the surface of the photocatalysts [2b,8a,19] . Figure S4 shows the XPS spectra of Mo 3d; the two peaks at 232.73 and 235.88 eV were assigned to Mo 3d 5/2 and Mo 3d 3/2 of Bi 2 MoO 6 , respectively [20] .…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the Fourier‐transform (FT)IR spectra displayed that the absorption bands of Bi−O bond and Mo−O bond of Bi 2 MoO 6 −Vo and Bi@Bi 2 MoO 6 are weaker than that of pure Bi 2 MoO 6 , indicating that both samples contain oxygen defects (Figure S3). Abundant oxygen vacancies on the surface of Bi 2 MoO 6 nanosheets not only change the chemical coordination of Bi 3+ ions to form metal nanoparticles, but also facilitate chemical adsorption of CO 2 molecules on the surface of the photocatalysts [2b,8a,19] . Figure S4 shows the XPS spectra of Mo 3d; the two peaks at 232.73 and 235.88 eV were assigned to Mo 3d 5/2 and Mo 3d 3/2 of Bi 2 MoO 6 , respectively [20] .…”
Section: Resultsmentioning
confidence: 99%
“…8(b) displays the DMPO‐•O 2 − ESR signal distribution of TiO 2 /Bi 2 MoO 6 . The signal strength of adduct heightens with prolonging the illumination time, which represents the concentration grade of •O 2 − 44, 45 . According to the above results, it can be concluded that the free radicals (•OH and •O 2 − ) with strong oxidizing ability can be generated on the surface of the composite materials, so the degradation rate of pollutants is improved by the high oxidation ability.…”
Section: Resultsmentioning
confidence: 83%
“…As shown in Fig. 9, there is no obvious ESR signal under dark conditions, suggesting that there is no production or transformation of •OH 45 . While lighting for 1 min, 5, and 10 min, the ESR signals of DMPO‐•OH are enhanced sharply for the composite.…”
Section: Resultsmentioning
confidence: 91%
“…reported semimetal bismuth mediated Bi 4 O 5 I 2 for CO 2 conversion [76] . The semimetal Bi also can be used as a co‐catalyst [77] . Then, the photo‐induced electron of Bi 4 O 5 I 2 converted to bismuth surface.…”
Section: Strategies For Optimizing Co2 Photoreduction Activitymentioning
confidence: 99%